TANTANGAN PEMBELAJARAN PKN DI SD PADA ERA DIGITAL DAN UPAYA PENINGKATANNYA - Fatin Ojes Nakmofa; Yohana Gaudensia Dhodhi Rema; Elisabet Vanesha Reta Reta; Pastela Sulastri Seja Seja; Deanatalis Padji Dogi Dogi; Fadil Mas’ud; Rahyudi Dwiputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the challenges and improvement strategies for Citizenship Education (PKn) in primary schools during the digital era using a descriptive qualitative approach and a systematic literature review. The findings indicate that limited digital competence among teachers, low levels of students’ digital and ethical literacy, and insufficient technological infrastructure and digital learning content are major obstacles to implementing technology-based PKn. Although students are digital natives, they remain vulnerable to misinformation and harmful online content, while teachers often struggle to integrate digital media with core civic values such as nationalism, ethics, and morality. The study recommends interactive learning media based on Pancasila, teacher training focused on critical digital literacy and cybersecurity, strengthening Digital Citizenship Literacy (PKD), and implementing digital formative assessments to authentically measure civic attitudes and behaviors. Overall, this research emphasizes the need for PKN to transform into an adaptive, innovative, and relevant learning model capable of shaping digitally responsible, ethical, and critically minded citizens.